Influence of the thermastabilization process and soak time during pyrolysis process on the polyacrylonitrile carbon membranes for O2/N2 separation - David, L. I. B.; Ismail, A. F. (Elsevier, 2003)
The hollow fiber membranes were fabricated using the dry/wet spinning process while polyacrylonitrile (PAN) carbon hollow fiber membranes were produced using inert gas pyrolysis process. The influences of the thermastabilization conditions and soak time on carbon membrane performance were investigated. It was observed that oxidative thermastabilization atmosphere produced carbon membranes with high stability while longer soak time improved the membrane selectivity and reduced the membrane's permeability.